Physicochemical And Nutritional Properties Of Nasi Lemak Prepared With Pumpkin Seed Milk - PPTI, Pusat Pengajian Teknologi Industri (Universiti Sains Malaysia, 2021)
Nasi lemak is one of Malaysians’ favorite meals which is frequently eaten during breakfast, lunch and even dinner. The usage of coconut milk that contains abundance of saturated fatty acids in nasi lemak can cause serious health implications on Malaysians who consume nasi lemak daily. Pumpkin seed milk is seen to have potential as an alternative to coconut milk due to its nutritional benefits and great amount of monounsaturated and polyunsaturated fatty acids. This research was conducted to investigate the possibility of substituting coconut milk with pumpkin seed milk in nasi lemak preparation. The nutritional composition and physical characteristics of nasi lemak prepared with pumpkin seed milk and coconut milk were analyzed in this study. The nasi lemak samples were cooked by replacing 225 mL of water with coconut milk, and pumpkin seed milk, that was cooked with 100 g of rice. The results obtained from proximate analysis showed that nasi lemak prepared with pumpkin seed milk contained significantly higher (p<0.05) fat (16.6%) and protein (6.4%) composition as compared to the nasi lemak prepared with coconut milk which are 11.9% and 3.1%, respectively. The L*, a*, and b* values obtained from color analysis for nasi lemak prepared with pumpkin seed milk are 71.36%, -3.93%, and 16.93% respectively while for nasi lemak prepared with coconut milk, the values are 77.01%, 0.20%, and 11.55% respectively. The hardness of nasi lemak prepared with pumpkin seed milk was also significantly higher than nasi lemak prepared with coconut milk. This study revealed that the nasi lemak prepared with pumpkin seed milk has the potential to replace coconut milk in nasi lemak preparation.